Promosi dan Pemasaran Digital Desa Wisata Cidugaleun Kecamatan Cigalontang Kabupaten Tasikmalaya - Nugraha, Agus Ramdhani; Saepuloh, Asep; Sukmaindrayana, Andri (Universitas Gajah Putih, Indonesia, 2023)
Digital promotion and marketing is very effective for introducing a product or service. By utilizing popular digital media, it is hoped that a product or service can be widely known by the public, both locally, nationally and even internationally. Cidugaleun Village is a village in Cigalontang sub-district, Tasikmalaya Regency, which is located at the foot of Mount Galunggung at an altitude of around 900 meters above sea level and has cool air and beautiful views. The view is dominated by vegetable plants and pine forests providing a green and beautiful atmosphere. Combined with the abundance of water and several waterfalls, this village is worthy of being developed into a mainstay tourist destination in Tasikmalaya Regency. In this activity, training was carried out for the young generation of Cidugaleun village under the auspices of Karang Taruna Giri Mukti so they were able to manage website content, take photos and videos, edit photos and videos and publish photos and videos on various media platforms that are currently popular. By utilizing their cell phone devices, the young generation of Cidugaleun village is given training so they can use cell phones to promote Cidugaleun village.